Current Practice Behaviors and Perceptions of Physiotherapist with Respect to Management of Individual with Osteoporosis - Komal Tariq, Iqra Waseem, Muhammad Nauman Hussain, Iqra Shahid, Ramesha Tahir, M. Ammar Ahmad Sohail (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the behaviors and perceptions of physiotherapist with respect to management of individual with osteoporosis. Study Design and Sampling Techniques: This was a cross sectional study with convenient sampling Study Settings & Participants: This study was conducted among physiotherapists working in University Institute of Physical therapy Clinics, Lahore, and Faisal hospital clinics, Faisalabad and Imran Idrees Institute of Rehabilitation Sciences, Sialkot. Data Collection Tools: A self-structured questionnaire focused on three aspects was used. First section was on physiotherapist concern for different types of treatment modes in osteoporotic patients, second section was on physiotherapist concern for manual therapy and third section was on physiotherapist concern about tissue injuries in response to manual therapy. Data Analysis: The data was analyzed using SPSS version 21. Results: The current study comprised of 100 physiotherapists 57(57 %) were female and 43(43 %) were male and 3% of respondents chosen the treatment modes such as ‘other’ as compared to others treatment modes. 75%of physiotherapists were using the strengthening exercises for treatment in osteoporotic patients. Forty one percent of physiotherapists were using the manual therapy 58% physiotherapists had showed up the concern with the use of manual therapy techniques as management for osteoporosis .This was more than half of the sample size taken for the study. Fifty one percent of physiotherapists had more concerned about muscle injuries and 71% were concerned about others injuries and fracture such as wrist fracture and hip fracture by using manual therapy. Conclusion: Use of slight progressive strengthening and exercise is better to overcome osteoporotic bone fractures due to manual force application during strength training in subjects with Osteoporosis Keywords: Behavior, Perception, Physiotherapist, Osteoporosis